Interest rate, liquidity and stock market performance in Ghana - Boachie, Micheal Kofi; Osei Mensah, Isaac; Opoku Frimpong, Albert; Ruzima, Martin (International Journal of Accounting and Economics Studies, 2016)
In this study, we examined the effect of interest rate and liquidity growth on stock market performance in Ghana using monthly data from the Ghana Stock Exchange and Bank of Ghana for the period 2010:12 to 2013:11. After employing robust linear regression (M-Estimation), there is a compelling evidence that performance of the Ghanaian stock market is highly influenced by liquidity growth, exchange rate and inflation; and that interest rate effect is insignificant though positive on the stock market index for the period under study.